Genetic rescue increases fitness and aids rapid recovery of an endangered marsupial population - Andrew R. Weeks (Nature Portfolio, 2017)
Genetic rescue can be valuable for the conservation of small populations threatened by low genetic diversity, but it carries the perceived risk of outbreeding depression. Here, Weeks et al. report increased hybrid fitness in a rescued population of the mountain pygmy possum, which likely contributed to population growth following genetic rescue.